Mechanisms of Therapeutic Resistance in Cancer (Stem) Cells with Emphasis on Thyroid Cancer Cells - Hombach-Klonisch, Sabine; Natarajan, Suchitra; Thanasupawat, Thatchawan; Medapati, Manoj R.; Pathak, Alok; Ghavami, Saeid; Klonisch, Thomas (Frontiers in Endocrinology, 2014)
Tissue invasion, metastasis and therapeutic resistance to anti-cancer treatments are common and main causes of death in cancer patients. Tumor cells mount complex and still poorly understood molecular defense mechanisms to counteract and evade oxygen deprivation, nutritional restrictions as well as radio- and chemotherapeutic treatment regimens aimed at destabilizing their genomes and important cellular processes. In thyroid cancer, as in other tumors, such defense strategies include the reactivation in cancer cells of early developmental programs normally active exclusively in stem cells, the stimulation of cancer stem-like cells resident within the tumor tissue and the recruitment of bone marrow-derived progenitors into the tumor (Thomas et al., 2008;Klonisch et al., 2009;Derwahl, 2011). Metastasis and therapeutic resistance in cancer (stem) cells involves the epithelial-to-mesenchymal transition- (EMT-) mediated enhancement in cellular plasticity, which includes coordinated dynamic biochemical and nuclear changes (Ahmed et al., 2010). The purpose of the present review is to provide an overview of the role of DNA repair mechanisms contributing to therapeutic resistance in thyroid cancer and highlight the emerging roles of autophagy and damage associated molecular pattern (DAMP) responses in EMT and chemoresistance in tumor cells. Finally, we use the stem cell factor and nucleoprotein High Mobility Group A2 (HMGA2) as an example to demonstrate how factors intended to protect stem cells are wielded by cancer (stem) cells to gain increased transformative cell plasticity which enhances metastasis, therapeutic resistance and cell survival. Wherever possible, we have included information on these cellular processes and associated factors as they relate to thyroid cancer cells.